Acute ischemic stroke for alteplase or medical care alone or intervention with/without alteplase in Palestine (AIS-AMI Palestine) - Habib, Mohammed (Journal of Cardiology and Cardiovascular Medicine, 2022)
Background: Stroke is the most common cause of permanent disability and the third most common cause of death in Palestine. We aimed to examine patterns of stroke presentation, causes, management and outcomes at the largest public Mistry of health hospitals in Palestine. Methods: Comprehensive data from all patients with acute ischemic stroke who were admitted to al-Shifa hospital between November 2021 and July 2022 and treated with alteplase alone or endovascular intervention with or without alteplase were prospectively collected and compare with acute ischemic stroke patients who were treated with medical care alone at Palestine medical complex hospital at 2018. Acute ischemic stroke presentation patterns, in-hospital evaluation and management, mortality, and morbidity were evaluated. Results: Medical care alone group: 138 patients with acute ischemic stroke, mean age was 65 ± 14 years and 49% were women. Most of the patients received antiplatelet therapy (98%), although none received thrombolysis. Only 17% received physical therapy evaluation. In-hospital mortality was 13%, and a modified ranking score of 0 -2 was in 44 patients (32%). Endovascular intervention with/without alteplase group: 56 patients with acute ischemic stroke. The mean age was 61 ± 12 years and 41% were women. All patients received brain computed tomography scans, although few received other investigations such as carotid Doppler (13%). Most patients with ischemic stroke received antiplatelet therapy (99%), although 39 patients (70%) received thrombolysis. Only 61% received physical therapy evaluation. In-hospital mortality was 7%. The modified ranking score 0 - 2: 32 patients (57%). Conclusion: This study conducted in Palestine showed that among patients with acute ischemic stroke, functional outcomes according to modified ranking score 0 - 2 were better by endovascular therapy with/without alteplase than with medical care alone.